Raspberry Pi 3 Based Self Troubleshooting Guide - THIYAGESAN M, BALAVIGNESH S, AVANTHIKA C, SHRILEKHA S, SWATHI R (Mathematical Statistician and Engineering Applications, 2022)
Given that not everyone has the knowledge to do small repairs oneself, not to mention the costs, we have suggested a Troubleshooting Guide for the most common washing machine issues to get it back to working. This concept focuses on offering a step-by-step manual to correct the operational faults[1]. This makes the self-troubleshooting manual for the appliances/vehicles a true necessity. This self-help manual includes a raspberry pi 3 that is installed on the device to achieve continuous operation monitoring[2,3]. The data of the consumer product is gathered by a barcode scanner in addition to the Android camera using the Raspberry Pi as the processor chip, and is then directed to a messaging app where the user can communicate about the capabilities of the item. To achieve them in real time, Open CV and Web sockets are used. Any user can talk with your Raspberry Pi Chatbot once the Raspberry Pi has been integrated with the bot[4]. The Raspberry Pi directs the user and finds the precise answer to the issue in accordance with the supplied inquiries. Following the chatbot's video streaming instructions, which are accurate since they are supported by augmented reality, will allow the user to fix that specific issue. As soon as the issue has been identified and fixed, the usual monitoring functions will resume. The Raspberry Pi assists the user in finding a technician by sending a prompt message to the selected washing machine maker in the event that the mistake cannot be identified and fixed and a technician is needed. The main goal of this project is to create a manual that will enable users to repair their gadgets without the assistance of specialists[5,9]. The suggested model is more reliable, more easily usable, and less expensive.